2017
DOI: 10.24875/ric.17002086
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Magnesium Intake is Significantly and Independently Associated with Higher Insulin Sensitivity in a Mexican-Mestizo Population: A Brief Cross-Sectional Report

Abstract: background: Magnesium acts as a cofactor in many intracellular reactions including phosphorylation of the insulin receptor;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This is consistent with the Dietary Reference Intakes (DRI) from the French Food Safety Agency, which recommended 6 mg/kg body weight of Mg intake per day. 28 A study from the United States also demonstrated that the dietary Mg intake requirement, which was 2.36 mg/kg per day, was related to body weight. 29 More studies are necessary to confirm whether weight-adjusted Mg intake is a better indicator for Mg intake.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the Dietary Reference Intakes (DRI) from the French Food Safety Agency, which recommended 6 mg/kg body weight of Mg intake per day. 28 A study from the United States also demonstrated that the dietary Mg intake requirement, which was 2.36 mg/kg per day, was related to body weight. 29 More studies are necessary to confirm whether weight-adjusted Mg intake is a better indicator for Mg intake.…”
Section: Discussionmentioning
confidence: 98%
“…Yu et al also showed an association between magnesium levels and HD patients’ responses to ESAs [ 23 ]. Previous studies have also suggested that improvements in insulin sensitivity, serum albumin levels, endothelial function, and the energy metabolism of erythrocytes may contribute to improvements in the responsiveness of ESAs via magnesium [ 24 , 25 , 26 ]. Our study did not include data on micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we decided to adjust the dietary Mg intake by body weight, and we found a significant association before and after the three-model adjustment. A study from Mexico also chose to adjust the Mg intake by body weight and found a significant result showing that the insulin sensitivity assessed by the Matsuda index was higher in the high dietary Mg intake group; however, the sample size of the study was small [26]. Given that the previous studies, which did not show a statistically significant correlation between dietary Mg intake and insulin resistance all used total dietary Mg intake instead of weight-adjusted dietary Mg intake, we assumed that the amount of dietary Mg an individual needed was related to his/her weight.…”
Section: Discussionmentioning
confidence: 99%